2019
DOI: 10.26434/chemrxiv.7700516.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Stable, Non-corrosive Perfluorinated Pinacolatoborate Mg Electrolyte for Rechargeable Mg Batteries

Abstract: Mg batteries are ap romising energy storage system because of the physicochemical merits of Mg as an anode material. However,t he lacko fe lectrochemically and chemically stable Mg electrolytes impedes the development of Mg batteries.I nt his study,anewly designed chloride-free Mg perfluorinated pinacolatoborate,M g[B(O 2 C 2 (CF 3 ) 4 ) 2 ] 2 (abbreviated as Mg-FPB), was synthesized by ac onvenient method from commercially available reagents and fully characterized.T he Mg-FPB electrolyte delivered outstandin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Cyclic voltammetry of MMC/(DME-G2) in a three-electrode setup using Pt disk as the working electrode reveals a low overpotential (<250 mV) for Mg plating similar to that of MMC/G4. Of particular interest is that very high current densities are observed for Mg stripping, approaching 100 mA cm 2 , an order of magnitude higher than that for MMC/G4 and also higher than those for any reported Mg electrolytes (20,31). The observed fast electrode kinetics is consistent with the improved overall bulk transport properties of the electrolyte solution.…”
mentioning
confidence: 71%
“…Cyclic voltammetry of MMC/(DME-G2) in a three-electrode setup using Pt disk as the working electrode reveals a low overpotential (<250 mV) for Mg plating similar to that of MMC/G4. Of particular interest is that very high current densities are observed for Mg stripping, approaching 100 mA cm 2 , an order of magnitude higher than that for MMC/G4 and also higher than those for any reported Mg electrolytes (20,31). The observed fast electrode kinetics is consistent with the improved overall bulk transport properties of the electrolyte solution.…”
mentioning
confidence: 71%
“…[ 12–14 ] Recently, some halogen‐free organic magnesium borate‐based electrolytes with high Mg plating/stripping efficiency, high voltage stability, and noncorrosive nature have been reported, but the practical application of these electrolytes suffers from complex synthesis and high cost. [ 15–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Recently, some halogen-free organic magnesium borate-based electrolytes with high Mg plating/stripping efficiency, high voltage stability, and noncorrosive nature have been reported, but the practical application of these electrolytes suffers from complex synthesis and high cost. [15][16][17] To solve these issues, researchers take efforts in exploiting other anode materials that possess well compatibility with conventional electrolytes to replace Mg metal anode, that is, developing magnesium-ion batteries (MIBs). [18][19][20] Among various anode materials for MIBs, Ti-based anode materials, such as TiO 2 , [21][22][23][24] Li 4 -Ti 5 O 12 , [25] Na 2 Ti 3 O 7 , [26] and Na 2 Ti 6 O 13 [27] have attracted much attention due to the good structural stability and suitable work voltage.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a polymer-type electrolyte for Mg/S system, it is necessary to select a proper polymerized anion which is nonnucleophilic and compatible with S, chemically stable and compatible with Mg, electrochemically stable to ensure a wide voltage window, and weakly-coordinated to cation which promises an efficient ion transport [36]. The non-polymerized fluorinated alkoxyborate anion based liquid electrolytes such as Mg[B(O2C2(CF3)4)2]2 [36], Mg[B(OCH(CF3)2)4]2 [18] and Ca[B(OCH(CF3)2)4]2 [37] et al have demonstrated a class of potential candidates in Mg or calcium (Ca) system. Because of the strong B-O bonds and the highly delocalized charge, this type of electrolytes normally has high anodic stability and high ionic conductivity [36].…”
Section: Introductionmentioning
confidence: 99%
“…The non-polymerized fluorinated alkoxyborate anion based liquid electrolytes such as Mg[B(O2C2(CF3)4)2]2 [36], Mg[B(OCH(CF3)2)4]2 [18] and Ca[B(OCH(CF3)2)4]2 [37] et al have demonstrated a class of potential candidates in Mg or calcium (Ca) system. Because of the strong B-O bonds and the highly delocalized charge, this type of electrolytes normally has high anodic stability and high ionic conductivity [36]. Various fluorinated alkoxyborate anions can be easily obtained via a simple reaction of strong basic BH4 − with different fluorinated alcohols [19].…”
Section: Introductionmentioning
confidence: 99%